2020
DOI: 10.3390/app10217875
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phosphorus on Cannabis sativa Reproduction, Cannabinoids, and Terpenes

Abstract: Many abiotic factors, such as mineral nutrients—including phosphorus (P)—fertility, can impact the yield and growth of Cannabis sativa. Given the economic portion of C. sativa is the inflorescence, the restriction of P fertility could impact floral development and quality could be detrimental. This study sought to track the impacts of varying P concentrations (3.75, 7.50, 11.25, 15.0, 22.50, and 30.0 mg·L−1) utilizing a modified Hoagland’s solution. This experiment examined plant height, diameter, leaf tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…This hypothesis is underpinned by the well-known production of multiple volatile organic compounds by Trichoderma species that promote the plant growth of plants [ 77 ] and the secretion of small molecules, such as polyketides, observed in Trichoderma harzianum T-22 [ 78 ]. Moreover, a second indirect pathway that might be beneficial for CBD content increase is the enhancement of phosphorus availability [ 79 ]. Trichoderma strains phosphate solubilization activity has been previously reported [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is underpinned by the well-known production of multiple volatile organic compounds by Trichoderma species that promote the plant growth of plants [ 77 ] and the secretion of small molecules, such as polyketides, observed in Trichoderma harzianum T-22 [ 78 ]. Moreover, a second indirect pathway that might be beneficial for CBD content increase is the enhancement of phosphorus availability [ 79 ]. Trichoderma strains phosphate solubilization activity has been previously reported [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“… Shiponi and Bernstein (2021a) found that 30 mg P per L was necessary for maximum dry mass after four weeks of vegetative growth in two high-THC Cannabis cultivars. In contrast, Cockson et al. (2020) found no increase in dry weight above 11 mg per L after eight weeks of vegetative growth in a high-CBD cultivar, despite P concentration in leaves nearly doubling as the P input increased from 11 to 30 mg per L.…”
Section: Introductionmentioning
confidence: 57%
“…Recent studies indicate that P in continuous liquid feed is adequate at about 15 mg per L for vegetative growth in greenhouse conditions with ambient CO 2 (Cockson et al, 2020;Veazie et al, 2021), but many studies, including this one, indicate higher levels of P are necessary for optimal reproductive growth (Bevan et al, 2021;Shiponi and FIGURE 3 Cumulative leached P over eight weeks of reproductive growth at input P of 25, 50 and 75 mg per L. Each point represents the total leached P of a leachate collection tray that contained three separate containers. Time series of P in the leachate at an input P of 25, 50 and 75 mg per L. Each line represents a sample taken from a leachate collection tray that contained three separate containers.…”
Section: Life-stage Affects Nutrient Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support that finding as plants that were fertilized with NPK outperformed unfertilized control plants in the amount of biomass produced, while at the same time exhibiting slightly higher N concentrations. It has been observed that the production of cannabinoids is limited by phosphorus ( Cockson et al, 2020 ) and that almost all of P acquired is found in inflorescences ( Shiponi and Bernstein, 2021 ). These latter authors also observed a negative correlation between floret yield and cannabinoid concentration and suggested, in line with Imo (2012) , that dilution was responsible for that negative concentration.…”
Section: Discussionmentioning
confidence: 99%